Finite element analysis of multiple asperity-to-asperity contacts. (1st January 2002) - Cheng, S.M.; Wu, X.J.
Multiple asperity-to-asperity contacts on wavy surfaces (contact, with friction, at midway of the sinusoidal wave) were analysed with finite element method (FEM). A parametric study was carried out for wave ratios (wavelength to amplitude) of 5, 10 and 20 and tension-to-pressure ratios of 0.1 and 1. It has been found that (i) each individual contact is typically Herzian; (ii) strong asperity interactions exist in the trough region, as the wave ratio decreases; (iii) on rough surfaces with low wave ratio, the maximum shear stresses tend to lie in parallel with or perpendicular to the axis of the main surface, thus having the tendency to produce parallel fretting scars and perpendicular cracks. These results qualitatively agree with the phenomena observed under wear/fretting fatigue conditions and shed light into fretting fatigue analysis.